THE RELATIONSHIP OF BEHAVIOR AND ATTITUDE OF WASHING HANDS USE SOAP WITH THE DIARRHEA INCIDENCE AT SDN GULUK-GULUK III, GULUK-GULUK TENGAH VILLAGE, GULUK-GULUK DISTRICT, SUMENEP REGENCY - Andi, Andi; Sasmito, Nanang Bagus; Santoso, Shelfi Dwi Retnani Putri (LPPM STIKes Bahrul Ulum Jombang, 2019)
Washing hand is often regarded as a trivial matter in society, whereas washing hands can contribute to improving society health status. School-age children have a habit of paying less attention to need to wash their hands in everyday life.. The purpose of this study is to know the behavior relationship and attitude of washing hand use soap with diarrhea incidence at SDN Guluk-Guluk III, Sumenep Regency. This research uses the analytical design with a cross sectional approach, with technique a total sampling. The results of the study obtained most of the students had negative behavior of 30 students (60.7%), Based on statistical tes there are behavioral relations with the incidence of diarrhea at SDN Guluk-Guluk III, Sumenep Regency, with a value of P-value (0.000) < (α: 0.05). There is a relationship with the incidence of diarrhea at SDN Guluk-Guluk III, Guluk-, Sumenep Regency with a value of P-value (0.00) < (α: 0.05). The prevention of diarrhea should be done by the students use of better sanitation, awareness of washing hand after playing or having. Keywords: behaviors, attitudes, diarrhea